2002
DOI: 10.1159/000057611
|View full text |Cite
|
Sign up to set email alerts
|

Renal Osteodystrophy in Predialysis and Hemodialysis Patients: Comparison of Histologic Patterns and Diagnostic Predictivity of Intact PTH

Abstract: Background: Comparison of renal osteodystrophy in predialysis and hemodialysis has been rarely reported. Distinct patterns of renal osteodystrophy could be found in these conditions. In addition the use of parathyroid hormone (PTH) and other markers for noninvasive diagnosis may result in different predictive values in predialysis and hemodialysis patients. Methods: 79 consecutive patients with conservative chronic renal failure and 107 patients on hemodialysis were studied. All patients were subjected to bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 18 publications
3
57
0
4
Order By: Relevance
“…The increased fracture risk among ESRD patients may relate to the more advanced underlying metabolic bone disease (CKD-mineral and bone disorder) observed in this population than in those with earlier stages of CKD (12,28). Of note, most of our patients had eGFR $30 ml/min per 1.73 m 2 , and although we did not have access to measures of mineral metabolism, other studies would suggest that even nondialysis patients with eGFR ,30 ml/min per 1.73 m 2 may not develop disordered mineral metabolism (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The increased fracture risk among ESRD patients may relate to the more advanced underlying metabolic bone disease (CKD-mineral and bone disorder) observed in this population than in those with earlier stages of CKD (12,28). Of note, most of our patients had eGFR $30 ml/min per 1.73 m 2 , and although we did not have access to measures of mineral metabolism, other studies would suggest that even nondialysis patients with eGFR ,30 ml/min per 1.73 m 2 may not develop disordered mineral metabolism (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The KDIGO CKD-MBD guideline recommends keeping the PTH level 2-9 times the upper limit of normal for the assay in dialysis patients (37) based on a number of bone biopsy studies which demonstrated that PTH poorly predicts underlying bone turnover within this range (38)(39)(40).Whilst a very low or very high PTH levels can predict low-turnover and high-turnover bone disease, PTH remains a poor marker of underlying bone histomorphometry within the target range. Alkaline phosphatase (ALP) may improve the sensitivity of PTH in predicting high/low bone turnover (41,42) and mortality in dialysis patients (43,44).…”
Section: Management Of Shpt In Ckdmentioning
confidence: 99%
“…Osteoartrit, kas krampları, kemik ağrısı, spontan kemik kırığı ve osteoporoz prevalansı üçüncü grupta daha yüksekti. HD hastalarımızın %30'u yaşam kalitesi soru formunu yardımcısız doldurdu ve ortalama fonksiyonel durum, psikolojik durum, ağrı ölçeği, yorgunluk ölçeği, global değerlendirme ve eklem sayımı sırasıyla 3 Psychological status: Scale of 0 to 10, 10 being impossible, on ability to get a good night's sleep, deal with feelings of anxiety or nervousness, and deal with depression or feeling blue.…”
Section: Study Design and Populationunclassified